Effects of Ficus deltoidea Jack and vitexin on pancreas, brain, kidney and bone of streptozotocin-induced diabetic rats - Samsulrizal, Nurdiana (2017)
Hyperglycaemia is the predominant cause of tissue damage and other systemic complications through oxidative stress. In diabetic patients, hyperglycaemia is associated with dearrangement of glycemic control. Limiting oxidative stress injuries using antioxidants therefore would be a logical approach to reduce hyperglycaemia and prevent further diabetes complications. Ficus deltoidea is a plant high in antioxidant compound content such as vitexin. Improvements in fasting blood glucose and antioxidant activities have indeed been reported following treatment with F. deltoidea and vitexin. However, the potential of F. deltoidea and vitexin in delaying diabetesrelated complications remains to be examined. In this regard, the study aimed to examine the effects of F. deltoidea and vitexin on the pancreas, brain, kidney and bone of streptozotocin (STZ)-treated rats. Intraperitoneal injection of STZ (60 mg/kg) was used to induce hyperglycaemia in rats. Methanol extract of F. deltoidea and vitexin was then given by oral-gavage for eight weeks. The effects of F. deltoidea and vitexin on the pancreas, brain, kidney and bone were further evaluated in four interlinked experiments. The novelty of this study is that Fourier transform infrared (FT-IR) spectroscopy has been introduced as a diagnostic approach to examine metabolic fingerprinting related to the tissue changes showing by biochemical and histological analysis, Morris Water Maze (MWM) test, micro-computed tomography (micro-CT) and fatty acid profiles. The present study demonstrates, for the first time, that F. deltoidea treatment was able to preserve pancreatic islet structure, improve learning and memory ability, mitigate renal injury and prevent bone loss in STZ-treated rats. It was also found that F. deltoidea resulted in a significant reduction in circulating amylin and an increase in serum insulin and osteocalcin levels. Additionally, the results showed that F. deltoidea treatment was associated with increased pancreatic, brain and kidney antioxidant activity. Although structural and functional improvement of the pancreas and brain was seen, vitexin treatment is associated with an increased risk of acute kidney injury and osteopenia. This might be explained by an increased serum fructose. In conclusion, F. deltoidea increased insulin secretion, in part, by reversing STZ-induced organ damage in the pancreas, brain, kidney and bone of rats. This could be related to the optimization of oxidant-antioxidant balance in the tissue.